Fiber reinforced polymer (FRP) pultruded shape structural connections - Sommer, Renee (Kansas State University, 2011)
This report discusses the two main types of structural connections used for fiber reinforced polymer (FRP) pultruded shapes, which are mechanical and bonded connections. The most common types of mechanical and bonded connections for FRP pultruded shapes are bolted and adhesively bonded joints respectively, and the advantages and disadvantages of each are discussed. Bolted connections are the most common type of connection used for FRP pultruded shapes and are therefore the focus of this report. Limit states and critical stresses for FRP bolted connections are explained along with the appropriate material properties that are needed to determine them. A simplified mechanics approach to determining the stresses in the FRP material and connection is presented along with a design procedure for FRP connections. A design example is given for a simple beam-to-column shear connection using three materials: FRP pultruded shapes, W-flange steel shapes, and wood sawn lumber in which the beam-to-column shear connection is compared. It is found that the FRP connection is comparable to the steel and wood connections, and all three are able to meet the requirements for the loading conditions given with reasonable results. Possible uses for FRP that would be more ideal than using steel or wood members are presented and areas that still need to be developed or require further research are discussed.
Keywords: FRP shapes; Connections; Architectural engineering (0462)